nagle_differential_equations_ISM_Part27

nagle_differential_equations_ISM_Part27 - Chapter 4 4 The...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Chapter 4 4. The corresponding homogeneous equation, y 00 + y = 0, has the associated auxiliary equation r 2 + r = r ( r + 1) = 0. This gives r = 0,- 1, and a general solution to the homogeneous equation is y h ( t ) = c 1 + c 2 e- t . Combining this solution with the particular solution, y p ( t ) = t , we find that a general solution is given by y ( t ) = y p ( t ) + y h ( t ) = t + c 1 + c 2 e- t . 6. The corresponding auxiliary equation, r 2 + 5 r + 6 = 0, has the roots r =- 3,- 2. Therefore, a general solution to the corresponding homogeneous equation has the form y h ( x ) = c 1 e- 2 x + c 2 e- 3 x . By the superposition principle, a general solution to the original nonhomogeneous equation is y ( x ) = y p ( x ) + y h ( x ) = e x + x 2 + c 1 e- 2 x + c 2 e- 3 x . 8. First, we rewrite the equation in standard form, that is, y 00- 2 y = 2 tan 3 x. The corresponding homogeneous equation, y 00- 2 y = 0, has the associated auxiliary equation r 2- 2 = 0. Thus r = ± √ 2, and a general solution to the homogeneous equation is y h ( x ) = c 1 e √ 2 x + c 2 e- √ 2 x . Combining this with the particular solution, y p ( x ) = tan x , we find that a general solution is given by y ( x ) = y p ( x ) + y h ( x ) = tan x + c 1 e √ 2 x + c 2 e- √ 2 x . 10. We can write the nonhomogeneous term as a difference ( e t + t ) 2 = e 2 t + 2 te t + t 2 = g 1 ( t ) + g 2 ( t ) + g 3 ( t ) . The functions g 1 ( t ), g 2 ( t ), and g 3 ( t ) have a form suitable for the method of undetermined coefficients. Therefore, we can apply this method to find particular solutions y p, 1 ( t ), y p, 2 ( t ), and y p, 3 ( t ) to y 00- y + y = g k ( t ) , k = 1 , 2 , 3 , respectively. Then, by the superposition principle, y p ( t ) = y p, 1 ( t ) + y p, 2 ( t ) + y p, 3 ( t ) is a particular solution to the given equation.particular solution to the given equation....
View Full Document

This note was uploaded on 02/12/2011 for the course MA 221 taught by Professor Mazmani during the Spring '08 term at Stevens.

Page1 / 5

nagle_differential_equations_ISM_Part27 - Chapter 4 4 The...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online